2020
DOI: 10.35568/naturalistic.v4i1.679
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Komik Digital Sebagai Media Edukasi Penanggulangan Bencana Alam

Abstract: Penelitian ini bertujuan untuk merancang dan mengembangkan  media pembelajaran atau bahan ajar komik digital. Media pembelajaran/ bahan ajar komik digital  yaitu model pembelajaran  yang merupakan salah satu alternatif yang dapat digunakan dalam pembelajaran Ilmu Pengetahuan Sosial (IPS), selain untuk meningkatkan motivasi dan hasil belajar siswa, mengoptimalkan pembagian kerja dalam kelompok, model ini dikembangkan untuk menghindari terjadinya berpikir abstrak, suatu kesan negatif yang dibiarkan terja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
1
5
0
2
Order By: Relevance
“…This shows the interest of students in learning to use the "Anima-lie" application. This can be in accordance with research that mobile learning applications are quite effective in increasing students' motivation in learning (Ningsih & Adesti, 2019;Ratnasari & Ginanjar, 2020). In addition, the "Anima-lie" application is able to provide opportunities for students to learn whenever and wherever it is not limited by space and time so that students have more frequency of repetition of material (Setyadi, 2017).…”
Section: Discussionsupporting
confidence: 84%
“…This shows the interest of students in learning to use the "Anima-lie" application. This can be in accordance with research that mobile learning applications are quite effective in increasing students' motivation in learning (Ningsih & Adesti, 2019;Ratnasari & Ginanjar, 2020). In addition, the "Anima-lie" application is able to provide opportunities for students to learn whenever and wherever it is not limited by space and time so that students have more frequency of repetition of material (Setyadi, 2017).…”
Section: Discussionsupporting
confidence: 84%
“…Other studies are not much different. (Andayani et al, 2020;Azizul et al, 2020;Harmawati et al, 2020;Kurniawati & Koeswanti, 2021;Ratnasari & Ginanjar, 2020;Sukmanasa et al, 2017) It also showed that the development of digital comics gets good to very good qualifications with high scores. The results obtained are related to the characteristics of the comic itself, which is the arrangement of ordered pictures and storytelling, which is an interesting thing for elementary school students.…”
Section: Discussionmentioning
confidence: 94%
“…Based on this, animal life cycle learning media using digital comics were developed for fourth-grade elementary school students. Digital comic media is a sequence of sequential images and presented digitally to convey information (Ratnasari & Ginanjar, 2020). As for the characteristics of comics, there are characters in the form of images that change poses, and there are speech balloons and backgrounds that match the comic story.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital comics are a visual-based media that can support learning because they contain storylines [12]. Digital comics were chosen because they have advantages that are suitable for use as learning media, such as creating student interest, presenting material more attractively, and being able to help students understand abstract concepts through storylines that cover the entire material [13].…”
Section: A Introductionmentioning
confidence: 99%